Mienie gmin i powiatów w Polsce w latach 1999-2005 - Obrębalski, Marek (Self-Government Property of Gminas and Poviats in Poland between 1999-2005, 2007)
The range of this article refers to material basis of tasks and competencies realization by self-government organs on gminas and poviats levels. The publication consists of statistical data and an analysis in the sphere of communal grounds, elements of technical and social infrastructure, communal dwelling stocks, organisational entities, fixed assets and budgetary incomes from gminas and poviats property. Property of gminas and poviats composes an important part of national property. Share of property which falls within gminas and poviats self-government cognisance is different by domains and territory. Importance of property of gminas and poviats in national and regional economy shows increasing tendency. It is an essential symptom of increasing role of self-government sector.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 444-456